The mitochondrial plasmid from Neurospora intermedia strain Labelle-1b contains a long open reading frame with blocks of amino acids characteristic of reverse transcriptases and related proteins. - Pande, S (1989)
We have determined the DNA sequence of the 4070 base pair mitochondrial plasmid from the Labelle-1b strain of Neurospora intermedia. Analysis of the sequence revealed that the plasmid contains a long open reading frame (ORF) that could encode a protein of up to 1151 amino acids. Codon usage in the long ORF shows no clear relationship to Neurospora mitochondrial genes, nuclear genes, nor to the ORF of a different Neurospora mitochondrial plasmid. The long ORF contains regions of similarity to yeast mitochondrial RNA polymerase as well as blocks of amino acids that are characteristic of reverse transcriptases and the ORFs of certain group II mtDNA introns (Michel and Lang, (1985) Nature 316,641). The plasmid gives rise to specific transcripts, some of which may be unit length, and which carry the information for expression of the long ORF. The genetic organization and content of the plasmid suggest that it is related to mobile genetic elements.